ANALISA KESTABILAN BENDUNGAN LOLAK 1 - Lontoh, Rheky Julistian; Manoppo, Fabian J.; Sompie, Oktovian B. A. (JURNAL SIPIL STATIK, 2020)
In order to support the national water security program, which is the fulfillment of raw water for households, cities and industries, and also for the efforts to reduce water damage due to flood in Bolaang Mongondow Regency, especially in Lolak Sub district, its carried out by construction of the Lolak Dam.In addition for many of the benefits that can be obtained by the construction of Lolak dam, there are also potential problems that can be caused by the impact of the dam construction that is a potential failure on the dam itself. The potential for dam failure in general can occur due to the influence of hydrology and hydraulics, due to the influence of water seepage and due to the influence of the structure.Through this paper, the author has analyzed in terms of the calculation of potential dam failure caused by the influence of hydrology and hydraulics, water seepage, and failure due to structural influences, among others by analyzing the effectiveness of foundation repairs using the grouting method, analyzing the stability of the dam to deformation , safety factor, for various kinds of scenarios (8 scenarios), as well as analyzing the stability of the dam to seepage and critical velocity of the body and foundation of the dam for conditions before and after soil improvement.The calculation and analysis of the stability of the dam is done using the PLAXIS 8.5 software. The parameters used in the PLAXIS analysis model are gunsat (gamma unsaturated), gsat (gamma saturated), E (modulus of elasticity), C (cohesion), Permeability (k), Poisson Ratio (n), Ã˜ ( shear angle) adjusted according to the dam design parameters planned, then juxtaposed with the required criteria and permitted safety factors.Â Keywords: Dam, Lolak Dam, Dam Stability, Soil Improvement.